PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. STRATINDO JAYA PACKAGING PEKANBARU - Lauren, Christine Lauren; ', Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to determine the effect of work motivation and work discipline on employee job satisfaction at PT. Stratindo Jaya Packaging Pekanbaru. work motivation (X1) and work discipline (X2). While employee job satisfaction (Y). In this study the method used was quantitative descriptive analysis with the SPSS program. The population in this study was 58 people, with the sample technique used was non-probability with the type of accidental technique. From the results of the tests carried out, it shows that work motivation has a positive and significant effect. Keywords : Work Motivation, Work Discipline, Employee Job Satisfaction